Severe congenital T-lymphocytopenia may affect the outcome of neonatal intensive care - Hulinkova, Ivana; Medova, Veronika; Soltysova, Andrea; Dobsinska, Veronika; Ficek, Andrej; Ciznar, Peter (Biomedical papers, 2024)
Aim. Circular DNA segments TREC (T-cell receptor excision circles) formed during T-lymphocyte maturation in the thymus, are a sensitive marker of thymic lymphocyte production in a broader manner. Quantification using qPCR is proposed as a surrogate marker of T cell malfunction in various primary and secondary conditions in a non-SCID selected risk newborn population. Methods. We collected 207 dry blood spot samples during the years 2015-2018, from newly admitted risk newborns. TREC values calculated per 106 cells were determined and a cut-off values of 5th percentile was set. The positive control group consisted of patients (n=13) with genetically confirmed SCID. Results. The median TREC value was 34,591.56 (18,074.08-60,228.58) for girls resp. 28,391.20 (13,835.01-51,835.93) per 106 cells for boys, P=0.046. Neonates born by C-section have been found to have higher TREC levels compared to neonates born by spontaneous delivery (P=0.018). In the group of preterm newborns (n=104), 3.8% had TREC value < 5th percentile, half of them died due to sepsis as opposed to no fatalities in preterm newborns with sepsis and TREC value > 5th percentile. In the group of term newborns (n=103) 9 children (8.7%) had TREC < 5th percentile, half of them were treated for asphyxia, with no fatal complications. Conclusion. TREC levels calculated for the 5th percentile of a risk neonatal group is suggested as a surrogate marker for increased risk of fatal septic complication. Early recognition of these newborns within a risk scoring system using TREC levels could lead to potentially lifesaving interventions.
Keywords: TREC; SCID; immunodeficiency; newborn screening; risk neonates